2023
DOI: 10.1002/anie.202302547
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the Synthesis Kinetics of Single‐Crystal Co‐Free Ni‐Rich Cathodes

Abstract: Non‐equilibrium kinetic intermediates are usually preferentially generated instead of thermodynamic stable phases in the solid‐state synthesis of layered oxides. Understanding the inherent complexity between thermodynamics and kinetics is important for designing high cationic ordering cathodes. Single‐crystal strategy is an effective way to solve the intrinsic chemo‐mechanical problems of Ni‐rich cathodes. However, the synthesis of high‐performance single‐crystal is very challenging. Herein, the kinetic reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 51 publications
0
16
0
Order By: Relevance
“…A recent study elucidated the growth mechanism of SC‐LiNi 0.95 Mn 0.05 O 2 (SC‐NM9505) with the assistance of Li 2 SO 4 as the flux agent. [ 74 ] In the CHTS process without Li 2 SO 4 , the fusion and grain growth of precursor particles started at temperatures above the melting point of LiOH (475 °C). Before the melting of LiOH, precursor, and LiOH are both solid, leading to a sluggish diffusion of metal ions and hindering the reaction kinetics, leading to heavy Li/Ni mixing.…”
Section: Preparation Strategies Of Sc‐ncmmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study elucidated the growth mechanism of SC‐LiNi 0.95 Mn 0.05 O 2 (SC‐NM9505) with the assistance of Li 2 SO 4 as the flux agent. [ 74 ] In the CHTS process without Li 2 SO 4 , the fusion and grain growth of precursor particles started at temperatures above the melting point of LiOH (475 °C). Before the melting of LiOH, precursor, and LiOH are both solid, leading to a sluggish diffusion of metal ions and hindering the reaction kinetics, leading to heavy Li/Ni mixing.…”
Section: Preparation Strategies Of Sc‐ncmmentioning
confidence: 99%
“…g) The formation mechanism of kinetic reaction pathway during synthesis of single-crystal Cofree Ni-rich oxides by molten salt method. Reproduced with permission [74]. Copyright 2023, Wiley-VCH.…”
mentioning
confidence: 99%
“…Crystallization is usually slow and residual grain boundaries may be present, leading to degradation of electrochemical properties. 24,137,138 Recent studies have revealed that the molten salt synthesis method promotes the rapid formation of layered structures from precursors at lower calcination temperatures. The surface of the precursor becomes sub-stable due to the strong polarizing forces provided by the molten salt, facilitating the insertion of Li + into the layers of the precursor to form layered oxides and reducing the formation energy of the stabile layered structure.…”
Section: Single-crystal Technologymentioning
confidence: 99%
“…[21][22][23] Notably, Ni-rich layered cathodes retain a great potential for commercialization due to their ability to produce Co-free materials. 15,[24][25][26] EVs will be powered primarily by LIBs. Consequently, the demand for power LIBs will be 10-20 times higher than it is now by 2030 (Figure 1A).…”
Section: Introductionmentioning
confidence: 99%
“…The most appropriate and successful strategies in recent years are the preparation of Co-free singlecrystal [52][53][54][55] or core-shell structures [56][57][58][59] and replacing the Co with other metal substitutions. 43,60 These approaches collectively aim to address the challenges associated with NCM cathodes and to improve electrochemical performance with good structural stability.…”
Section: Introductionmentioning
confidence: 99%